2018
DOI: 10.1080/10837450.2018.1455698
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of letrozole-loaded poly(d,l-lactide) nanoparticles for drug delivery in breast cancer therapy

Abstract: Letrozole (LTZ), an aromatase inhibitor used for the treatment of hormonally-positive breast cancer in postmenopausal women, has poor water solubility, rapid metabolism, and a range of side effects. In this study, polymer-based nanoparticles (NPs) incorporating the drug have been designed and characterized, aimed to control the release, potentially maximize the therapeutic efficiency, and minimize the side effects of the drug. LTZ was incorporated into poly(d,l-lactide) (PDLLA) NPs by employing the emulsion-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Obtained particles were spherical in shape with a size of 350 nm. High entrapment efficiency was obtained (96%) and the release profile was significantly improved [23].…”
Section: Figure 3 Formation Of O/w Emulsion By Single Emulsion Evaporationmentioning
confidence: 94%
“…Obtained particles were spherical in shape with a size of 350 nm. High entrapment efficiency was obtained (96%) and the release profile was significantly improved [23].…”
Section: Figure 3 Formation Of O/w Emulsion By Single Emulsion Evaporationmentioning
confidence: 94%
“…By successfully preventing aromatase which produces oestrogen, LET slows down the growth of hormone-responsive breast tumours in vivo. However, research has shown that LET has some negative effects on patients, including diarrhoea, constipation, fever, fatigue, and chest pains [3]. Regarding its overall effects on human health, LET was reported to possess potential efficacy that could be enhanced by advancing in combination with other chemotherapeutic agents [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Alginate is a biocompatible natural hydrophilic polysaccharide polymer isolated from marine brown algae. It has been reported that it increases the wettability of hydrophobic drug molecules [29,30], and accordingly, it has been used successful in delivering and encapsulating thiadiazole-based compounds [31,32,33,34]. Generally, the encapsulation of drugs with polymers is one of the versatile methods in controlling drug release over a long period of time and solves the complications related to traditional drug administration methods in chemotherapy.…”
Section: Introductionmentioning
confidence: 99%